EGFR-IL-6 Signaling Axis Mediated the Inhibitory Effect of Methylseleninic Acid on Esophageal Squamous Cell Carcinoma - Wang, Yu; Liu, Xianghe; Hu, Guanghui; Hu, Chenfei; Gao, Yang; Huo, Miaomiao; Zhu, Hongxia; Liu, Mei; Xu, Ningzhi (Frontiers in Pharmacology, 2021)
Epidemiological and experimental evidence indicate that selenium is associated with a reduced risk of some cancers, including esophageal cancer. However, the exact mechanism is still unclear. In the present study, we used esophageal squamous cell carcinoma (ESCC) cell lines and animal models to explore the anti-cancer mechanism of methylseleninic acid (MSA). Firstly, MSA treatment dramatically attenuated Epidermal Growth Factor Receptor (EGFR) protein expression but did not alter mRNA levels in ESCC cells. On the contrary, EGFR overexpression partly abolished the inhibitory effect of MSA. With a microRNA-array, we found MSA up-regulated miR-146a which directly targeted EGFR, whereas miR-146a inhibitor antagonized MSA-induced decrease of EGFR protein. We further used 4-nitroquinoline-1-oxide (4NQO)-induced esophageal tumor mice model to evaluate the inhibitory effect of MSA in vivo. MSA treatment significantly decreased the tumor burden and EGFR protein expression in tumor specimens. Furthermore, MSA treatment inhibited EGFR pathway and subsequntly reduced Interleukin-6 (IL-6) secretion in the supernatant of cancer cell lines. MSA-induced IL-6 suppression was EGFR-dependent. To further evaluate the association of IL-6 and the anti-tumor effect of MSA on esophageal cancer, we established the 4NQO-induced esophageal tumor model in IL-6 knock-out (IL-6 KO) mice. The results showed that IL-6 deficiency did not affect esophageal tumorigenesis in mice, but the inhibitory effect of MSA was abolished in IL-6 KO mice. In conclusion, our study demonstrated that MSA upregulated miR-146a which directly targeted EGFR, and inhibited EGFR protein expression and pathway activity, subsequently decreased IL-6 secretion. The inhibitory effect of MSA on esophageal cancer was IL-6 dependent. These results suggested that MSA may serve as a potential drug treating esophageal cancer.